Manajemen Utang untuk Perencana Keuangan Perusahaan (Target Generasi Z) - ,; ,; ,; ,; ,; ,; ,; , (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2023)
Debt management is an aspect of financial planning that is very important for corporate financial planners to pay attention to, especially Generation Z who will become financial planners in the future. The purpose of financial planning is to manage the company's financial resources effectively and efficiently in order to achieve the set business goals. The dedication team conveyed debt management to corporate financial planners using the pulpit lecture method and open discussions. The implementation of this activity is supported by PT Ciera Cahaya Harmoni as the company's business consultant. The results of the activity show that the debt management knowledge of the participants is still limited and has been conditioned by debt management material from the dedicated team, the pulpit lecture method and open discussions have proven to be effective in increasing debt management knowledge for participants and financial planners for generation Z companies must have a good understanding of debt management such as identifying funding needs, determining appropriate funding sources, managing risk, optimizing capital structure and monitoring financial performance.